Power demand and supply management in microgrids with uncertainties of renewable energies - Wang, Ran (2014)
An important task of power demand and supply management in microgrids is to maintain a good match between power generation and consumption at the minimum cost. Since the highly fluctuant renewable energies constitute a significant portion of the power resources in microgrids, the microgrid system central controller (MGCC) faces the challenge of effectively utilizing the renewable energies while fulfilling the requirements of customers. To tackle the problem, a novel power demand and supply management scheme is proposed in this paper, which mainly includes three parts as follows. Firstly, a novel uncertainty model is developed to capture the randomness of renewable energy generation which, by introducing a reference distribution according to past observations and empirical knowledge and defining a distribution uncertainty set to confine the uncertainty of renewable energies, allows the renewable energies to fluctuate around the reference distribution. An optimization problem is then formulated to determine the optimal power consumption and generation scheduling for minimizing the fuel cost. Finally, a two-stage optimization approach is proposed to transform and then solve the prime problem. Numerical results indicate that the proposed scheme helps effectively reduce the energy cost. Detailed studies on the impacts of different factors on the proposed scheme provide some interesting insights which shall be useful for policy making for the future MGCC.